2020
DOI: 10.1136/bmjopen-2019-033495
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of total knee replacement in addition to non-surgical treatment: a 2-year outcome from a randomised trial in secondary care in Denmark

Abstract: ObjectiveTo assess the 24-month cost-effectiveness of total knee replacement (TKR) plus non-surgical treatment compared with non-surgical treatment with the option of later TKR if needed.Methods100 adults with moderate-to-severe knee osteoarthritis found eligible for TKR by an orthopaedic surgeon in secondary care were randomised to TKR plus 12 weeks of supervised non-surgical treatment (exercise, education, diet, insoles and pain medication) or to supervised non-surgical treatment alone. Including quality-adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…A recent trialbased economic evaluation of total knee arthroplasty observed 68% of surgical candidates randomized to an exercise therapy intervention have not proceeded to surgery 2 years after the study period. 53 This exercise and education program would pay for itself if 8% of people with knee OA avoided a total joint replacement. 54 An integrated pathway aligning with OA clinical guidelines would be cost-effective in multiple health systems but could be cost saving if total joint replacement were avoided.…”
Section: Discussionmentioning
confidence: 99%
“…A recent trialbased economic evaluation of total knee arthroplasty observed 68% of surgical candidates randomized to an exercise therapy intervention have not proceeded to surgery 2 years after the study period. 53 This exercise and education program would pay for itself if 8% of people with knee OA avoided a total joint replacement. 54 An integrated pathway aligning with OA clinical guidelines would be cost-effective in multiple health systems but could be cost saving if total joint replacement were avoided.…”
Section: Discussionmentioning
confidence: 99%
“…The management of KOA usually starts with non-drug treatment (e.g., education and exercise) and medications (e.g., nonsteroidal anti-inflammatory drugs, NSAIDs), and ends up with joint replacement surgery [ 4 6 ]. Due to undesirable side effects of long-term pharmacological treatments and knee surgery [ 7 – 9 ], complementary and alternative medical (CAM) therapies are increasingly used [ 10 ]. Acupuncture treatment represents the most popular CAM therapy [ 11 , 12 ], evidence from clinical trials and systemic reviews has suggested that acupuncture can be effective in treating pain and dysfunction in patients with KOA [ 9 , 13 – 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A care pathway in which exercise therapy is employed prior to knee replacement complies with guideline recommendations while also being cost-effective. [5][6][7][8][9][10]64 We have previously argued that the premise for exercise therapy before potential surgery to enhance postoperative outcomes in patients eligible for knee replacement should be questioned 33 as several systematic reviews conclude no clinically relevant effect. 33,[65][66][67][68][69][70][71][72][73][74] In line with this and based on the results from the QUADX-1 trial, we suggest the use of exercise therapy within the ERAS concept is to "pre-evaluate" to promote shared decision-making in an enhanced care pathway for patients with severe knee OA rather than to "prepare" patients for surgery.…”
Section: Discussion (Generalizability Interpretation)mentioning
confidence: 99%
“…49,[74][75][76][77][78][79][80][81][82][83] Instead of being a predetermined care pathway (leading to surgery), exercise therapy before potential surgery could be used to inform the shared decision-making process when planning a care pathway, 8,17,18 which complies with guideline recommendations while being costeffective. [5][6][7][8][9][10]84 Based on the results from the QUADX-1 trial, we suggest using simple (one exercise) homebased resistance exercise therapy within the ERAS concept to "pre-evaluate" the need for surgery in patients with severe knee OA rather than to "prepare" patients for surgery.…”
Section: Secondary Outcomesmentioning
confidence: 99%